Case of early childhood‐onset narcolepsy with cataplexy: Comparison with a monozygotic co‐twin. Issue 5 (October 2014) - Ito, Hiromichi; Mori, Kenji; Mori, Tatsuo; Goji, Aya; Kagami, Shoji
Abstract We describe here a rare case of early childhood‐onset (5 years of age) narcolepsy. This case was interesting because of the ability to compare the patient's symptoms to the condition of her healthy monozygotic co‐twin sister. The only environmental difference between the co‐twins was head injury, which may be associated with the presence of narcolepsy. The co‐twin was extroverted, sociable, reliable, and dexterous. In contrast, the patient could be described as introverted, gentle, honest and persevering, but was weak at conversation, assessment of a situation, memory, planning, activity (she was inactive), a sense of time, understanding of an analog clock, operating efficiency, and physical education (due to obesity). The sisters showed the same degree of appetite and dexterity with their fingers. Narcolepsy is often under‐recognized or underdiagnosed, especially when the onset occurs in childhood. When we observe preschoolers with excessive daytime sleepiness, we should consider the possibility of narcolepsy with cataplexy.